2019
DOI: 10.3390/w11061291
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Hydrologic Benefits of a Bioswale in Brunswick County, North Carolina (NC), USA

Abstract: Bioswales are a promising stormwater control measure (SCM) for roadway runoff management, but few studies have assessed performance on a field scale. A bioswale is a vegetated channel with underlying engineered media and a perforated underdrain to promote improved hydrologic and water quality treatment. A bioswale with a rip-rap lined forebay was constructed along state highway NC 211 in Bolivia, North Carolina, USA, and monitored for 12 months. Thirty-seven of the 39 monitored rain events exfiltrated into und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The authors distinguished between those variables affecting the drainage area, such as the discharge area, the discharge ratio and the main concentration at the swale inlet; those variables associated with the swale itself, such as the swale length, slope, type of soil, vegetation and operational life. This research also revealed the limitations of previous work, emphasizing the need for continuous and long-term monitoring alongside later work such as Purvis et al [12]. Most of the investigations carried out in the literature show a limited number of storm events which introduces a certain level of uncertainty, as they miss the major hydrological effects influenced by the climate on the location, the rainfall and temperature patterns and the seasonality.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…The authors distinguished between those variables affecting the drainage area, such as the discharge area, the discharge ratio and the main concentration at the swale inlet; those variables associated with the swale itself, such as the swale length, slope, type of soil, vegetation and operational life. This research also revealed the limitations of previous work, emphasizing the need for continuous and long-term monitoring alongside later work such as Purvis et al [12]. Most of the investigations carried out in the literature show a limited number of storm events which introduces a certain level of uncertainty, as they miss the major hydrological effects influenced by the climate on the location, the rainfall and temperature patterns and the seasonality.…”
Section: Introductionmentioning
confidence: 62%
“…This study represents one of the largest studies presenting data from three complete hydrological years and 19 storm events captured for detailed analysis during the 6 months stage where on-site weather data were available. Therefore, resulting in a longer period than other significant studies recently published such as those by Leroy et al [34], Purvis et al [12], Lisenbee et al [29] and Andrés-Valeri et al [33], amongst others.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The DSS predicted the most promising results from the BS in terms of land use utilization to meet 10-year frequency targeted discharge (0.12 m 3 /s), with the peak outflow rate of 0.113 m 3 /s and a smaller footprint (0.72 ha) than other types. The BS structure is often designed for better conveyance, collection, and infiltration of stormwater runoff [60]. The structure is highly vegetated with grass throughout its length and sloped sides to improve the surface runoff and infiltration, which was also encountered in our modeled bioswale.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction effect of roof runoff by LID practices and their combination need to be evaluated in detail to test their effectiveness and support LID selection, planning and decision making. The hydrological effect of most individual LID practices at the building scale has been fully studied by many previous experimental and observational studies [6,8,[15][16][17]. Many models have been used to simulate the effect of individual LID practices, and some of these models can perfectly reproduce the hydrological performance of actual LID [18][19][20].…”
Section: Introductionmentioning
confidence: 99%